Protection of family and inheritance rights : materials of the Round Table (29 April 2025 р., Odesa) - (:unkn) unknown (Odesa : Yurydychna literatura, 2025)
The collection contains abstracts of scientific reports of the participants of the round table, prepared within the framework of the English-language educational component and devoted to a comprehensive analysis of theoretical and practical problems of the protection of family and inheritance rights. The volume reflects contemporary scientific approaches in the relevant field, contributes to the development of professional legal terminology in English, and may be used in scientific, educational, and practical activities. Збірник містить тези наукових доповідей учасників круглого столу, підготовлені в межах англомовного освітнього компоненту та присвячені комплексному аналізу теоретичних і практичних проблем захисту сімейних та спадкових прав. Видання відображає сучасні наукові підходи у відповідній сфері, сприяє розвитку фахової правничої термінології англійською мовою та може бути використане в науковій, навчальній і практичній діяльності.
Захист сімейних та спадкових прав : матеріали круглого столу (29 квітня 2025 р. м Одеса)
Protection of family and inheritance rights : materials of the Round Table (29 April 2025 р., Odesa). Odesa, 2025. 84 p. URL: https://hdl.handle.net/11300/32698
Keywords: правове регулювання; юридична відповідальність; правова система; державне управління; соціальні відносини; правозастосування; нормативно-правові акти; публічне право; правові норми; захист прав; legal regulation; legal responsibility; legal system; public administration; social relations; law enforcement; normative legal acts; public law; legal norms; protection of rights